Indonesian Strategic Collaborative Governance : a Dynamic Multiple Helix Concept - Budiati, Ayuning; Jumiati, Ipah Ema; Rahmawati, Rahmawati; Arenawati, Arenawati (Social and Political Science Faculty - Universitas Tidar, 2023)
Indonesian collaborative governance has been very popular since the year-2000. Amongst public, private organizations, academics, media and societies. However, at present, collaboration amongst those actors have not been popularly conducted with communities, such as hobbies communities or even alumni communities. As the source of budgeting sector resources, those communities are very strategic actors to improve collaboration in a dynamic way as multi helix collaboration. This research uses qualitative approach and descriptive analysis method. The result of this research is that there is a strategic need to improve the role of communities in enhancing the advantages of collaboration in the multi helix concept.